Simulation of adhesion conditions on road vehicles - Jilek, Petr; Voltr, Ondřej; Pokorný, Jan (Ústav termomechaniky AV ČR, v. v. i., 2016)
The article deals with the possibilities of controlled affecting of adhesion in the contact between vehicle wheel and road. In the first part some of currently used ways of affecting of adhesion are stated. These are briefly compared subsequently. Further new proposal of system for affecting of adhesion is introduced followed by its comparison with SkidCar system. The proposed system and SkidCar system are simulated in simplified form and resultant behavior of the car is evaluated in enclosed graphs. The article is processed in primary version of particular system for verifying of vehicle stability. This article aims to highlight the fact that it is possible to change the adhesive conditions of road vehicles using an additional system without preventing the movements of a body.
Simulace adhezních podmínek silničního vozidla
Keywords: simulation; adhesion conditions; road vehicle; simulace; adhezní podmínky; silniční vozidlo